A new dual-ferrite–assisted hybrid reluctance machine with two-stage excitation for starter generator application - Xiong, Shu; Yang, Yucui; Pan, Jian (Frontiers in Energy Research, 2022)
Reluctance machines with DC field coil in stator are a competitive candidate for starter generation application, due to the elimination of rare-earth permanent magnet (PM), robust structures, and controllable excitation. However, due to the poor excitation ability of DC field coils, the torque density is disadvantageous. Moreover, with the increase in the DC field current, it is exposed to the risk of extra DC saturation in stator teeth. As a consequence, the torque density and efficiency are both constrained. To solve the aforementioned problems, based on the comprehensive consideration of production cost and torque performance, this study proposed a novel type of hybrid reluctance machine with dual-ferrite–assisted in stator slots. The inner-layer ferrite PM is magnetized tangentially, which can effectively achieve the DC-saturation–relieving effect, while the outer-layer ferrite PM is magnetized radially to increase the machine torque density through the flux modulation effect. Based on finite element analysis, the machine torque density and efficiency can be improved by 20 and 5%, respectively. Furthermore, to simplify the excitation system of the DC terminal, a two-stage excitation method is proposed by splitting some turns of armature winding to feed DC field winding with passive rectifier. No power switching devices are needed for the excitation system in this way, making the system highly robust. The effectiveness of the proposed design is verified by time-stepping finite element analysis.